Adhesion Anisotropy: Controlled Adhesion Anisotropy between Two Rectangular Grooved Surfaces (Adv. Mater. Interfaces 24/2018). Issue 24 (20th December 2018) - Liu, Zheyu; Tao, Dashuai; Zhou, Ming; Lu, Hongyu; Meng, Yonggang; Tian, Yu
Abstract : The adhesion anisotropy between two rectangular grooved (RG) surfaces can be varied over 100 times by changing the alignment state due to the modulating of the contact area. An extra relative shearing in the lateral direction can enhance this adhesion. This strategy has a great potential to be used in flexible connectors and switchable grippers. More details can be found in the article number1801268 by Zheyu Liu, Yu Tian, and co‐workers.